Three strategies of transgenic manipulation for crop improvement - Yu, Haoqiang; Yang, Qingqing; Fu, Fengling; Li, Wanchen (Frontiers in Plant Science, 2022)
Heterologous expression of exogenous genes, overexpression of endogenous genes, and expression suppressing of undesirable genes are the three strategies of transgenic manipulation for crop improvement. Up to 2020, the most (227) of the singular transgenic events (265) of crops approved for commercial release worldwide have been developed by the first strategy. Thirty-eight of them have been transformed by synthetic sequences transcribing antisense or double-stranded RNAs and three by mutated copies for expression suppressing of undesirable genes (the third strategy). By the first and the third strategies, hundreds of transgenic events and thousands of varieties with significant improvement of resistance to herbicides and pesticides, as well as nutritional quality, have been developed and approved for commercial release. Their application has significantly decreased the use of synthetic pesticides and the cost of crop production and increased the yield of crops and the benefits to farmers. However, almost all the events overexpressing endogenous genes remain at the testing stage, except one for fertility restoration and another for pyramiding herbicide tolerance. The novel functions conferred by the heterologously expressing exogenous genes under the control of constitutive promoters are usually absent in the recipient crops themselves or perform in different pathways. However, the endogenous proteins encoded by the overexpressing endogenous genes are regulated in complex networks with functionally redundant and replaceable pathways, and are difficult to confer the desirable phenotypes significantly. It is concluded that heterologous expression of exogenous genes and expression suppressing of undesirable genes are superior to the overexpression of endogenous genes for transgenic improvement of crops.